Resilience of physical components in flood-prone areas in Kelantan / Ezzat Fahmi Ahmad, Ida Nianti Mohd Zin and Kartina Alauddin - Ahmad, Ezzat Fahmi; Mohd Zin, Ida Nianti; Alauddin, Kartina (2021)
The functionality and ability of physical components such as energy, water and waste, transportation, telecommunication and building to sustain during floods are very crucial to communities in flood-prone areas. As known, floods in Kelantan are not only a regular occurrence but also extreme. Thus there is an urgent need to have resilient physical components. The resilience of physical components is an ability to resist, absorb, accommodate and recover from the effect of flood in a timely and efficient manner. Therefore, the objective of this paper is to determine the most important infrastructure systems for the community in flood-prone areas in Kelantan. Thus, a cross-sectional survey was conducted among one hundred and fifty-one (151) communities (government = 40; private sectors = 38; learning institution = 31; and communities = 32) in eight (8) districts which identified as flood-prone areas in Kelantan. A total 17 factors (energy = 3; water and waste = 3; transportation = 4; telecommunication = 4; and buildings = 3) for infrastructure systems were analyzed by SPSS version 22 subjected to descriptive analysis. The result obtained from the analysis found that building component is the most importance physical component for community in flood-prone areas in Kelantan.